Estimação de metas estratégicas por meio de análise por envoltória de dados e modelo da Barganha de Nash: aplicação na área de saúde publica - Santos, Marco Aurélio Reis dos [UNESP] (2014)
This work focuses the empirical estimation of targets for internal medicine from UBS (Basic Health Unit) in Guaratinguetá city. It was proposed a method that can help Public Health service managers to identify problems and best practices in each Basic Health Units where people are attended. In the first step, under the guidance system of strategic management BSC it was defined performance indicators based on its four perspectives that translate the vision and the strategic of health service. In the second step, using the DEA method, it was compared technical efficiency of medical services in order to define the goals and identifier the medical services benchmark. Finally, it was identified alternatives projections of targets for performance indicators, according to a negotiation whose solution was defined by the Nash Bargaining Model. This approach provides the execution of an agreement between the DMUs with the best relationship of commitment among goals. From the point of view practical and theoretical, the results were promising and offer alternatives in order to solve the problems that were identified in Basic Health Units. It can show the potentiality of the method developed for applications in different economic organizations. Among the contributions of this thesis, it can highlight the solution of problems related to the effect of multiobjective approaches in common incommensurability, and to propose adequate procedures in nonlinear models that make its practical application, ensuring the optimal global